Pengaruh Motivasi Terhadap Minat Mahasiswa Akuntansi untuk Mengikuti Pendidikan Profesi Akuntansi (PPAK) di Propinsi Lampung - Rosmiaty Tarmizi; Julia Restuti (Jurnal Akuntansi dan Keuangan, 2015)
This study aims to analyze and provide empirical evidence about the effect of motivation onstudent interest in accounting to follow accounting education program. Hypothesis in this research is motivation influence of student interest in accounting to follow accounting education program. The data used in this study is primary data. The primary data used by using questionnaire obtained from 90 respondents is S1 students majoring in accounting at the University of Lampung Province who have taken 120 credits or who was in the seventh semester. Samples were obtained by proportional sampling. The data analysis technique used in this study is a simple regression analysis and hypothesis testing t test using SPSS 18.0 for windows. Results of the study was the hypothesis is accepted as motivation affect the interest of the education of accounting students to follow the accounting profession.